2019
DOI: 10.1007/s10974-019-09510-4
|View full text |Cite
|
Sign up to set email alerts
|

Colon 26 adenocarcinoma (C26)-induced cancer cachexia impairs skeletal muscle mitochondrial function and content

Abstract: Cancer cachexia is characterized by a rapid ‘loss of muscle with or without loss of fat mass'1 that can impede cancer treatments resulting in significantly increased mortality rate in afflicted individuals. Whereas impaired skeletal muscle respiratory capacity likely plays a role in cancer‐induced fatigue, few studies have evaluated mitochondrial function in models of cancer cachexia2, and none in the well‐characterized colon 26 carcinoma (C26)‐induced cancer cachexia model. The present study thus aimed to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 27 publications
6
25
0
Order By: Relevance
“…Additional genes annotating to this category are involved in apoptosis, including Alkbh7 and Mtfp1 , and two genes encoding mitochondrial ribosomal proteins, Mrpl34 and Mrpl45 . This reduced expression of mitochondria‐related genes in the DIA of PDAC‐PDX mice aligns with published studies, which show mitochondrial deficits in cachectic tumour‐bearing hosts including altered mitochondrial biogenesis, fission/fusion, mitophagy, and mitochondrial function . Importantly, our findings are also consistent with repression of mitochondrial‐related genes in the skeletal muscle of cachectic PDAC patients …”
Section: Resultssupporting
confidence: 92%
“…Additional genes annotating to this category are involved in apoptosis, including Alkbh7 and Mtfp1 , and two genes encoding mitochondrial ribosomal proteins, Mrpl34 and Mrpl45 . This reduced expression of mitochondria‐related genes in the DIA of PDAC‐PDX mice aligns with published studies, which show mitochondrial deficits in cachectic tumour‐bearing hosts including altered mitochondrial biogenesis, fission/fusion, mitophagy, and mitochondrial function . Importantly, our findings are also consistent with repression of mitochondrial‐related genes in the skeletal muscle of cachectic PDAC patients …”
Section: Resultssupporting
confidence: 92%
“…Recently published work from Neyroud et al demonstrated increased mitochondrial uncoupling and a reduction in mitochondrial respiratory capacity in the soleus muscle of cachectic C26 tumor-bearing mice [6]. In an extension of those findings, we show here compromised mitochondrial function in the heart and diaphragm of cachectic C26 tumor-bearing mice.…”
Section: Discussionsupporting
confidence: 85%
“…Although the underlying mechanisms driving cancer-induced cardiorespiratory muscle weakness remain unknown, emerging evidence reveals that cancer promotes mitochondrial damage, resulting in alterations to electron transport chain complex activity, impaired ATP synthesis and the production of reactive oxygen species (ROS) [6]. Additionally, mitochondrial impairment in muscle tissue has been shown to cause profound functional and structural disorganization [7][8][9].…”
Section: Research Papermentioning
confidence: 99%
“…Accordingly, mitochondrial respiration rate is also reduced in isolated mitochondria from skeletal muscle of cachectic cancer mice compared with control mice. 192,195,196 Therefore, animal studies clearly indicate that the entire mitochondrial oxidative pathway is profoundly impaired by cancer cachexia.…”
Section: Skeletal Muscle Metabolism In Animal Models Of Cancer Cachexiamentioning
confidence: 99%